Microcontroller-Based Digital Body Height Measuring Tool with Display Information - Haryanto, Dadang; Yulianeu, Aneu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This research was conducted to make a digital body height measuring device based on the arduino uno microcontroller with information display using an LCD, this tool is expected to help the process of measuring body height become easier, practical, and obtain more accurate results. The system development method uses research and development which aims to produce products from research. Products produced based on needs analysis. Research procedures and data collection using needs analysis, literature studies, and small-scale research. The testing method uses black box testing which aims to test the specific functions of the designed software. The results of the research and trials of the digital body height measuring tool with the HC-SR04 ultrasonic sensor based on the arduino uno microcontroller can work properly with an accuracy of 99.73% and an error of 0.009%.